2020
DOI: 10.2147/cmar.s255482
|View full text |Cite
|
Sign up to set email alerts
|

<p>High Level of IL-10 in Cerebrospinal Fluid is Specific for Diagnosis of Primary Central Nervous System Lymphoma</p>

Abstract: Purpose The pathological diagnosis of primary central nervous system lymphoma (PCNSL) by stereotactic brain biopsy and craniotomy is not often applicable due to the high cost and associated complications. In recent years, some biomarkers in cerebrospinal fluid (CSF), including interleukin 10 (IL-10), microRNAs, CXC chemokine ligand 13 (CXCL13), have been reported to be associated with PCNSL. However, this conclusion was controversial. Therefore, this study was to test whether Th17 cell-related cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…IL10 and IL6 are important protective cytokines which were secreted after inflammation and immune responses, which reduce cellular damage and promote the cellular repair process. More studies ( Ramkumar et al, 2012 ; Nguyen-Them et al, 2016 ; Shao et al, 2020 ) have shown that PCNSL has a greater relationship with IL-10 and IL-6. Especially IL-10, which is an important biomarker for PCNSL, elevated concentrations of IL-10 in the CSF make PCNSL more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…IL10 and IL6 are important protective cytokines which were secreted after inflammation and immune responses, which reduce cellular damage and promote the cellular repair process. More studies ( Ramkumar et al, 2012 ; Nguyen-Them et al, 2016 ; Shao et al, 2020 ) have shown that PCNSL has a greater relationship with IL-10 and IL-6. Especially IL-10, which is an important biomarker for PCNSL, elevated concentrations of IL-10 in the CSF make PCNSL more aggressive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that potential PCNSL biomarkers include microRNAs (miR-21, miR-101, and 548b). Among them, miR-222 has a certain value for the early detection of diffuse large B-cell lymphoma [20], as do soluble CD19, interleukin (IL-10), and chemokine ligand 13 (CXCL13), but further validation and screening are required to replace brain biopsy [21,22]. (3) In this case, the use of steroids and gamma globulin after the initial diagnosis may have caused atypical pathological changes that led to 2 biopsies for diagnosis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Shao et al defined an IL-10 cut-off level of 8.3 pg/mL, providing a sensitivity and specificity for the diagnosis of PCNSL of 59.0% and 98%, respectively. Interestingly, the inclusion of IL-6 in a combined ratio IL-10/IL-6 ratio at a cut-off of 1.6 increased the sensitivity and specificity to 66.0% and 91%, respectively [ 20 ]. Similar data were reported by Sasagawa et al for IL-10 with a cut-off of 3 pg/mL, providing a sensitivity and specificity of 94.7% and 100%, respectively [ 19 ].…”
Section: Il-10 and Il-6mentioning
confidence: 99%